1998
DOI: 10.1093/oxfordjournals.schbul.a033348
|View full text |Cite
|
Sign up to set email alerts
|

The Russian Concept of Schizophrenia: A Review of the Literature

Abstract: The focus of this article is a comprehensive review of the Russian-Soviet conceptualization of schizophrenia, which can be understood only in the broader historical and cultural context of Russian-Soviet psychiatry. Because of multiple barriers and the political abuse of psychiatry in the former Soviet Union, international psychiatric literature has lacked unbiased data about the scientific merit and historical logic of the Russian-Soviet concept of schizophrenia. This article represents an attempt to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 64 publications
0
33
0
1
Order By: Relevance
“…In the "Moscow school" of psychiatric diagnosis, a configural approach is used for schizophrenia whereby the course and the current syndrome are considered separately, and latent forms of schizophrenia are routinely diagnosed (Calloway, 1988(Calloway, , 1993Lavretsky, 1998;Smulevich, 1989;Snezhnevskii, 1983). For example, clinicians distinguish between slowly progressive, episodic, and attack-like course types in addition to the more familiar distinctions between syndrome types such as catatonic and paranoid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the "Moscow school" of psychiatric diagnosis, a configural approach is used for schizophrenia whereby the course and the current syndrome are considered separately, and latent forms of schizophrenia are routinely diagnosed (Calloway, 1988(Calloway, , 1993Lavretsky, 1998;Smulevich, 1989;Snezhnevskii, 1983). For example, clinicians distinguish between slowly progressive, episodic, and attack-like course types in addition to the more familiar distinctions between syndrome types such as catatonic and paranoid.…”
mentioning
confidence: 99%
“…It was beyond the scope of this study to investigate the relationship of specific diagnoses to one another or to evaluate the validity of the diagnoses. (For further details in English about the Moscow school of psychiatry and various points of view on the diagnosis of schizophrenia in the Soviet Union and Russia, see Andreyev, 1986;Calloway, 1988Calloway, , 1993Lavretsky, 1998;Reddaway, 1978;Smulevich, 1989). All three diagnostic systems were used in this study because there was no empirical or expert consensus that any one system was preferable as the "gold standard" to use in validating the psychological measures.…”
mentioning
confidence: 99%
“…In October 1951, several leading Soviet neuroscientists and psychiatrists were charged with practising 'anti-Pavlovian, anti-Marxist, idealistic, reactionary' science (Lavretsky 1998). The defendants had to admit in public to their wrongdoing and several were dismissed from their posts.…”
Section: Anti-marxist Reactionary Sciencementioning
confidence: 99%
“…The authors reviewed nine studies of CCU that showed impaired abstract reasoning, concept formation, and mental flexibility. 1 ECF may represent a very relevant target for rehabilitation strategies, since ECF deficits are associated with poorer outcomes in treatment. 2 In addition, the literature discussing whether ECFrelated deficits persist after a period of abstinence is contradictory.…”
Section: Evidências De Déficits Executivos Persistentes Após Um Mês Dmentioning
confidence: 99%
“…Note that the systematic abuse of the field of psychiatry is not synonymous with political abuse. Causes of this abusive mishandling may include low standards of training and practice, inadequate quality assurance procedures, 1 and poorly implemented legislation given that professionals are not trained to use the new laws 2 and because they are not motivated enough to follow them. We have previously reported a case study 3 illustrating the overdiagnosis of schizophrenia: the diagnostic criteria of sluggish schizophrenia has been misused in the Soviet Union, thus affecting many people who have nothing to do with politics.…”
mentioning
confidence: 99%